New Neogene taxa of the tribe Chlamydini Teppner, 1922 (Pectinidae, Bivalvia) of southern South America. (November 2019) - Santelli, María B.; del Río, Claudia J.
Abstract: The Chilean species traditionally assigned to the genera Chlamys Röding, 1798 or Zygochlamys Ihering, 1907 are now placed in two new endemic South American taxa: Dietotenhosen n. gen. (middle Miocene–early middle Pliocene), to include the southeastern Pacific Ocean species D . hupeanus (Philippi, 1887) n. comb. and D . remondi (Philippi, 1887) n. comb., and Ckaraosippur n. gen. (earliest middle Miocene–Pliocene), for C . calderensis (Möricke, 1896) n. comb. (Chile) and C . camachoi n. sp. (Argentina). Both genera are the youngest survivors of the tribe Chlamydini in southern South America. None of them is related to the circumpolar genus Psychrochlamys Jonkers, 2003, and the previous proposal of the dispersal through the Antarctic Circumpolar Current for the species included herein in Dietotenhosen is rejected. UUID:http://zoobank.org/61b4bb50-321f-4b78-9069-609178ef0817